2014
DOI: 10.1108/cpoib-06-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

A critical perspective on corporate social responsibility

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Purpose -The purpose of this paper is to outline the structural limits of corporate social responsibility (CSR) and develop a framework for the global governance of CSR. Permanent repository linkDesign/methodology/approach -The paper adopts a critical perspective on emerging discourses of CSR in developing a governance framework.Findings -Win-Win situations do not capture the complexities of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 23 publications
2
82
0
5
Order By: Relevance
“…Failure to deliver those projects undermines the citizen's welfare, and leads to the loss of billons of rands. It has been revealed that the extent of these failures varies within and across the country, driving national, and global inequalities (Bobby Banerjee, ). The Good Governance Learning Network () revealed that public perceptions on local government are negative; the results show that the level of trust in local government is in the minority at 48.1%.…”
Section: Challenges Of Political Influence In Local Governmentmentioning
confidence: 99%
“…Failure to deliver those projects undermines the citizen's welfare, and leads to the loss of billons of rands. It has been revealed that the extent of these failures varies within and across the country, driving national, and global inequalities (Bobby Banerjee, ). The Good Governance Learning Network () revealed that public perceptions on local government are negative; the results show that the level of trust in local government is in the minority at 48.1%.…”
Section: Challenges Of Political Influence In Local Governmentmentioning
confidence: 99%
“…First of all, as already recognized by Hoffrén and Apajalahti (), research is still fragmented in analyzing to what extent, and how, practical implementation of activities relates to the CSL objectives stated by agribusiness companies. Specifically, questions remain open on the stakeholder engagement and monitoring activities in place to enforce that agribusiness companies actually implement the planned activities (Banerjee, ) and reach the hoped outcomes in relation to CSL. These knowledge gaps justify the focus of this article, which aims to assess—through a review of company reports—the linkages between stated CSL goals, practical implementation strategies, stakeholder engagement approach, and plans for monitoring.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Multistakeholder initiatives, standards and guidelines along with the increasing presence of private actors that constitute the governance of resource extraction cannot address authority, capability and representation gaps, which often leads to conflict (Banerjee, 2014). As we have seen earlier structural and discursive power asymmetries between local communities and mining companies mean that the latter group along with their industry associations have greater authority and capability to participate in governance.…”
Section: ---------------------------------------------------Insert Tamentioning
confidence: 99%